2008
DOI: 10.1002/art.23311
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological development of children born to patients with antiphospholipid syndrome

Abstract: Objective. To verify the occurrence of learning disabilities (LDs) in the offspring of women with primary antiphospholipid syndrome (APS) as a consequence of fetal exposure to maternal antiphospholipid antibodies (aPL), and to evaluate the impact of maternal chronic disease on children's development. Methods. We studied 17 children of mothers with primary APS using a standardized intelligence test (Wechsler Intelligence Scale for Children, Revised), a specific LD battery of tests (Sartori, MT groups' test for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 32 publications
0
26
1
Order By: Relevance
“…However, an increased prevalence of LD or behavioural problems failed to be confirmed by more recent studies on children born to mothers with anti-Ro/SSA, even when subgrouped for NL manifestations and exposure in utero to dexamethasone [143,144]. The exposure to maternal aPL was also linked to LD in children born to both mothers with SLE [139] and with APS [145]; prematurity was not associated with LD in these studies.…”
Section: The Offspring Of Sle/aps Patientscontrasting
confidence: 51%
“…However, an increased prevalence of LD or behavioural problems failed to be confirmed by more recent studies on children born to mothers with anti-Ro/SSA, even when subgrouped for NL manifestations and exposure in utero to dexamethasone [143,144]. The exposure to maternal aPL was also linked to LD in children born to both mothers with SLE [139] and with APS [145]; prematurity was not associated with LD in these studies.…”
Section: The Offspring Of Sle/aps Patientscontrasting
confidence: 51%
“…Between 1992 and 1999, three case-control studies of infants born to mothers with APS showed that there was no statistically significant difference in severe and minor neonatal complications, which were mainly related to prematurity. 33,35,36 In one of these studies there was no adverse outcome related to APS and at paediatric follow-up all children were normal on neurodevelopmental and physical examination. 31 Another retrospective study of 55 newborns of mothers with primary APS showed that the majority of neonatal complications were closely linked to prematurity.…”
Section: Neurodevelopmental Outcome Of Children Born To Mothers With mentioning
confidence: 97%
“…Multivariate analysis showed that APS is associated with a threefold to eightfold increase in any use of SE services, consistent with a prior report of increased LD in offspring of patients with primary APS. 4 …”
mentioning
confidence: 99%